2015
DOI: 10.1007/s00381-015-2742-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide field flooding reduces the hemodynamic effects of venous air embolism occurring in the sitting position

Abstract: Our preliminary study shows that a CO2-enriched sitting position surgical microenvironment significantly reduces the hemodynamic effects of VAE, more likely because arterial CO2 emboli are more soluble and consequently much better tolerated than air emboli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…41 Longatti et al in their preliminary study of 10 cases suggested that a CO 2 -enriched surgical field decreased the hemodynamic effects of VAE, since CO 2 emboli are more soluble and therefore better tolerated than air emboli. 42 Matjasko et al reported a significantly higher incidence of VAE in children (62%) compared with adults (23%); however, a retrospective comparison between adults and children undergoing suboccipital craniotomy in the sitting position by Cucchiara et al showed a lower incidence of VAE in children (16 of 48) than in adult controls (22 of 48). 43,44 Bithal et al similarly reported the incidence as 22% in children and 28% in adults out of a total of 430 patients (96 children and 334 adults) who underwent posterior fossa surgery in the sitting position.…”
Section: Complicationsmentioning
confidence: 97%
“…41 Longatti et al in their preliminary study of 10 cases suggested that a CO 2 -enriched surgical field decreased the hemodynamic effects of VAE, since CO 2 emboli are more soluble and therefore better tolerated than air emboli. 42 Matjasko et al reported a significantly higher incidence of VAE in children (62%) compared with adults (23%); however, a retrospective comparison between adults and children undergoing suboccipital craniotomy in the sitting position by Cucchiara et al showed a lower incidence of VAE in children (16 of 48) than in adult controls (22 of 48). 43,44 Bithal et al similarly reported the incidence as 22% in children and 28% in adults out of a total of 430 patients (96 children and 334 adults) who underwent posterior fossa surgery in the sitting position.…”
Section: Complicationsmentioning
confidence: 97%
“…La irrigación del campo con dióxido de carbono se ha utilizado para reducir los efectos hemodinámicos del EAV [23]. El catéter con balón intrajugular también se usa para prevenir el EAV [24].…”
Section: Complicaciones Asociadas Con La Posición Sentada A) Embolia Aérea Venosa (Eav)unclassified